The New Age in Glastonbury : the construction of religious movements - Prince, Ruth (Berghahn Books, 2000)
The New Age movement is a twentieth-century socio-cultural phenomenon in the Western world with Glastonbury as one of its major centers. Through experimentation with a number of ways of analyzing this movement, the authors were able to develop a novel theory of social religious movements of broad applicability. Based around contradictions relating to such central anthropological concepts as communitas, egalitarianism, individualism, holism, and autonomy, it reveals the processes by which, having abandoned a mainstream lifestyle, people come to build up a counter-cultural way of life. Drawing on their own work on tribal shamanistic religions, the authors are able to point out interesting similarities between the latter and the Glastonbury New Age movement. Not only that: their model allows them to explain such wide-ranging social and religious movements as the Hutterites, the Kibbutz, and Green communes. In fact, the authors argue, these movements may be regarded as variations of the Glastonbury type. -- from back cover.
Keywords: New Age movement.; Glastonbury (England) -- Religion.; England -- Religion.; Nouvel Âge (Mouvement); Angleterre -- Religion.; RELIGION / General; New Age movement; Religion; England; England -- Glastonbury